The Legal Certainty of Legitimate Ownership in Copyright Works of Songs or Music, as well as Associated Rights in Non-Declarative Recording in accordance with the Royalty Management System under Government Regulation No. 56 of 2021 (Case Study on Copyrigh - Litoama, Fransiskus; Purgito (Yayasan Sinergi Kawula Muda, 2024)
The non-registration of data on song or music creators and related rights in the Directorate General of Intellectual Property (DJKI) database and the Song and Music Information System (SILM) could lead to legal uncertainty regarding the economic rights of song or music creators and related rights in claiming royalty rights. This research aims to explore the legal consequences of a song or music copyright/related rights that are not registered in the SILM and the dispute resolution patterns as efforts to provide legal protection for unregistered song or music copyrights/related rights in the SILM. The applied method is empirical sociology to assess the effectiveness of legal instruments in accordance with applicable regulations by observing the research objects and the level of their implementation in practice. The results indicate that for works of music or songs not recorded in the SILM, royalty payments are made voluntarily by users with the condition of not creating new records, and dispute resolution patterns involve mediation through the PPNS before proceeding to litigation to seek a win-win solution.